P692 Gentamicin susceptibility to neisseria gonorrhoeae in malawi after twenty-five years of sustained use. (14th July 2019) - Chen, Jane; Matoga, Mitch; Massa, Cecilia; Ndalama, Beatrice; Jere, Edward; Krysiak, Robert; Chikaonda, Tarsizio; Hobbs, Marcia; Cohen, Myron; Hoffman, Irving
Abstract : Background: Gentamicin has been used exclusively for the treatment of Neisseria gonorrhoeae (GC) in Malawi, since 1993. Previous gentamicin susceptibility testing in 1993, 1996 and 2007, showed ≥95% susceptibility by both agar dilution and E-test. However, clinical cure rates 1–2 weeks following treatment, have been in the 90% range. We are in the process of repeating this assessment to inform treatment guidelines. Methods: We are enrolling HIV-infected men presenting with acute urethritis at the sexually transmitted infections (STI) clinic at Bwaila District Hospital in Lilongwe, Malawi. All participants provide urethral swabs for STI etiologic testing, and are treated syndromically per Malawian standard of care, with gentamicin 240 mg IM, doxycycline 100 mg, BID for 7 days, and metronidazole 2g single dose. Patients are seen one week post-treatment for repeat clinical exam and GC culture. All specimens with a positive GC culture are tested locally for gentamicin susceptibility via E-test. E-test inhibition with ranges from 0-4, 4-16, and ≥16 are categorized as high, moderate, and low susceptibility, respectively. Clinical cure is determined by genital examination. Results: 42 men with gonococcal urethritis have been enrolled to date. Baseline gentamicin E-test results: high susceptibility: 0-1: 21%; 1-2: 60%; 2-4: 19%; moderate or low susceptibility ≥4: 0%. 37/42 men (88%) returned for follow-up. 4/37 (11%) were culture positive for GC, including 2 (5%) symptomatic men. 3/4 (75%) of the week one E-test results were in the high susceptibility range, and 1/4 (25%) was in the low susceptibility range (≥16). Conclusion: Based on our E-test results, all of the baseline GC isolates appear to be susceptible to gentamicin. However, at one-week follow-up, ∼11% continued to be infected with GC. Determining if these are treatment failures, re-infections or new infections is a challenge. Laboratory comparisons of matched isolates are planned to help categorize these concerning results. Study enrollment continues. Disclosure: No significant relationships.